CRITICAL STUDY OF MUTRAVAHA SROTAS AND URINE FORMATION WITH MODERN REVIEW (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is the ancient advanced medical system, a branch of Atharva Veda which provides mantra for human health and cure. Ayurveda also engrid several theories and concepts related to the human anatomy and physiology. In this regards Ayurveda has mentioned anatomical and physiological perspectives related to the various system and Mutravaha srotas is one of them. The Mutravaha Srotas described in many Samhitas and vedas for collection and excretion of Mutra (urine). To understand the physiology of mutravaha srotas and various organs related to mutra nirmiti (formation) and uthsarjana (excretion) with ayurvedicand contemporary view. Though there was no technical advancement, still vision of aptajana about mutra nirmiti is highly commendable. Ahara is a key of Prana dharana, after aharapaak it transformed into saar (nutritive part) and kitta (less nutritive part). Saar bhag nutures the dhatus (body tissues) and kitta bhag transformed in mutra and purisha (faeces).The process of urine formation in ayurveda is contradictory with contemporary view, hence in attending article the author has tried to prove the scientific significance of ayurveda concept of mutra nirmiti with reference of different samhitas, vedas and modern litrerature.